Strategi manajerial pemeliharaan preventif peralatan medis dalam meningkatkan Keandalan diagnosis - Aldi Situngkir Situngkir; Rian Andriani; Yen Efawati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The reliability of laboratory diagnoses is significantly influenced by the performance and readiness of medical equipment. In healthcare facilities with remote geographic locations such as Wedabay Medical Center (WMC) in North Maluku, preventive maintenance of medical equipment is a crucial strategy for maintaining service quality and avoiding service disruptions due to equipment failure. Purpose: To formulate a managerial strategy for preventive maintenance to improve diagnostic reliability. Method: The study used a qualitative approach with a case study design. Data were obtained through in-depth interviews, observations, maintenance document reviews, and focus group discussions (FGDs). Informants were selected using purposive sampling from laboratory staff, medical personnel, and management. Data analysis was conducted descriptively using a reduction, presentation, and verification model, and was supported by a SWOT analysis. Results: Preventive maintenance has been implemented routinely with the support of management commitment and a regular schedule. However, challenges remain, such as limited technical resources, vendor dependence, remote location, and suboptimal documentation. Conclusion: Recommended strategies include strengthening the documentation system, optimizing vendor collaboration, and developing a more structured maintenance management system. These strategies contribute to improving diagnostic reliability and the quality of laboratory services.   Keywords: Diagnostic Reliability; Managerial Strategy; Medical Equipment; Preventive Maintenance.